Improvement of the Methodology of Forming the Financial Result of the Organization in the Conditions of Economic Transformation - I. Zhilyakov, Dmitry (2021)
The relevance of the research topic is determined by the fact that in a market economy, obtaining income and expenses is the direct goal of the enterprise, since it is the profit that creates guarantees for the existence and development of the organization. Significant changes occurring both in the macroeconomic aspect and at the level of an individual organization require an immediate solution to issues related to the optimization of production activities, namely, maximizing income and minimizing costs. The experience that the organizations have faced has shown to a greater extent the need to improve the methodological approach to the formation of financial results.